Wood consumption rates of forest species by subterranean termites (Isoptera) under field conditions - Peralta,Regina Célia Gonçalves (2004)
Termites are well -known for their capacity to damage and destroy wood and wood products of all kinds in the tropics and subtropics. A field test was undertaken to evaluate variations in wood consumption of Pinus sp. and three species of Eucalyptus by subterranean termites. The test consisted of wooden stakes of each species being initially submitted to water immersion for 0, 24, 48 and 72 h, and buried in the ground to natural infestation by subterranean termites for an exposure period of 30, 45 and 60 days. Three species of subterranean termites were identified: Heterotermes longiceps (Snyder), Coptotermes gestroi (Wasmann) (Isoptera: Rhinotermitidae), and Nasutitermes jaraguae (Holmgren) (Isoptera: Termitidae). This is the first record of occurrence of H. longiceps in the state of Rio de Janeiro. Although the wood-consumption rates were not correlated significantly with their wood densities, there was a tendency of the softwoods (E. robusta and Pinus sp.) to be more consumed by subterranean termites than the woods of intermediate hardness (E. pellita and E. urophylla). Among the eucalyptus, E. robusta showed to be more susceptible to attack by subterranean termites than E. pellita and E. urophylla